Rancang Bangun Sistem Informasi Monitoring Dan Evaluasi Desa Mandiri Pangan Pada Badan Ketahanan Pangan Provinsi Jatim - Salam, Achmad Febriyan; Sulistiowati, Sulistiowati; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Food insecurity and poverty is still a major problem in Indonesia is becoming. To that end, the Agency Food Ketahahan through the sub fields of food insecurity on food program launches Independent Villages (Demapan). (25/Permentan/OT 140/2/2012). Monitoring and evaluation of the independent village of food itself is done gradually starting from the level of village, district, County and province. Monitoring and evaluation conducted by the clerk of the village of all hardcopy form or in the form of paper.  This can cause a buildup of data result in lost data or corrupted due to the computerized yet.. Based on the above issues, hence the need for a system of Monitoring and evaluation of the Independent Village of food On the body of the East Java Province food security is a system that is designed to help the Sub fields of food insecurity in terms of monitoring and evaluation Demapan. This system uses media website to facilitate coordination officer of village, district, County to the province. So expect the existence of this system can further accelerate the process of monitoring and reporting activities the village Self-sufficient food becomes a problem on a sub field of food insecurity province of East Java